A study of variation in serum lipid levels in patients with Plasmodium vivax malaria - P., Prashanth Kumar; Nazareth, Rashmi Amans Flora (International Journal of Advances in Medicine, 2020)
Background: Malaria is a common protozoal infection. Plasmodium vivax malaria is the most common species distributed worldwide and in India. The vivax malarial infection is associated with various haematological and biochemical abnormalities, anaemia and thrombocytopenia among the frequently identified abnormal parameters. However vivax malaria is also associated with abnormal lipid levels including low cholesterol levels and normal to high serum triglyceride levels. Methods: This study is a cross-sectional observational study including 100 inpatients admitted to Medical College Hospital over a period of 18 months diagnosed with Plasmodium vivax malaria. The patients were selected based on inclusion and exclusion criteria. The relevant data was collected and analysed. Results: Vivax malaria infection was found to be more common among males (80%) and during third decade of life (51%). HDL Cholesterol was decreased in all cases, LDL Cholesterol and Total Cholesterol was also decreased in nearly all patients with only 1% cases having values above normal range. Serum Triglycerides was elevated more than 150 mg/dl in 69% cases with 25% cases having values above 200mg/dl. The hypocholestrolemia and hypertriglyceridemia were directly proportional to the thrombocytopenia, hyperbilirubinemia, elevated serum creatinine levels and parasite load. Conclusions: This study demonstrates the presence of altered serum lipid levels in the form of hypocholesterolemia and hypertriglyceridemia in cases of Plasmodium vivax malaria mono infection. This study also shows that the above lipid alterations were found to be deranged to greater extent in clinically, haematologically and biochemically severe form of infections.